Efficient Exploration for Dialogue Policy Learning with BBQ Networks & Replay Buffer Spiking - Lipton, Zachary C.; Gao, Jianfeng; Li, Lihong; Li, Xiujun; Ahmed, Faisal; Deng, Li (2016)
When rewards are sparse and action spaces large, Q-learning with ϵ -greedy exploration can be inefficient. This poses problems for otherwise promising applications such as task-oriented dialogue systems, where the primary reward signal, indicating successful completion of a task, requires a complex sequence of appropriate actions. Under these circumstances, a randomly exploring agent might never stumble upon a successful outcome in reasonable time. We present two techniques that significantly improve the efficiency of exploration for deep Q-learning agents in dialogue systems. First, we introduce an exploration technique based on Thompson sampling, drawing Monte Carlo samples from a Bayes-by-backprop neural network, demonstrating marked improvement over common approaches such as ϵ -greedy and Boltzmann exploration. Second, we show that spiking the replay buffer with experiences from a small number of successful episodes, as are easy to harvest for dialogue tasks, can make Q-learning feasible when it might otherwise fail.
arXiv:1608.05081